2015
DOI: 10.3855/jidc.6626
|View full text |Cite
|
Sign up to set email alerts
|

Survival of enteroaggregative Escherichia coli and Vibrio cholerae in frozen and chilled foods

Abstract: Introduction: Enteroaggregative Escherichia coli (EAEC) and Vibrio cholerae are common bacteria that infect people in developing countries. Nowadays, food preservation by freezing and refrigeration are very common practices that extend the shelf life of food products. Unfortunately, EAEC and V. cholerae are suspected to survive at low temperatures. Methodology: Various foods and beverages used as samples were artificially inoculated with EAEC and V. cholerae pure colonies and incubated at room temperature (27°… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…Tahoun et al 23 , Sharma et al 24 , and Islam et al 25 also found higher results. This is corroborated by findings from Waturangi et al 26 who found that V. cholerae could survive for at least three months in all items tested, including UHT milk and ice cream that was kept in a freezer.…”
Section: Discussionsupporting
confidence: 83%
“…Tahoun et al 23 , Sharma et al 24 , and Islam et al 25 also found higher results. This is corroborated by findings from Waturangi et al 26 who found that V. cholerae could survive for at least three months in all items tested, including UHT milk and ice cream that was kept in a freezer.…”
Section: Discussionsupporting
confidence: 83%
“…In raw shrimp with an initial count of 5 log CFU/g, a survival of between 4 and 9 days was observed at 5 and 10 ºC, respectively (Pesigan et al, 1967). In freezing, a V. cholerae survival greater than 3 months has been verified according to temperature (ICMSF, 1996) (Waturangi et al, 2015). In fresh foods, including freshwater fish, V. cholerae O1 remains viable for up to 90 days at -5 ºC and up to 30 days at -25 ºC.…”
Section: Storage Temperaturementioning
confidence: 99%
“…The sensitivity of the primes was tested with serial of dilution of the V. cholerae and E. coli (EHEC and ETEC) genomics, which was serially diluted from 10 ng; 5 ng; 1 ng; 0.5 ng; 0.25 ng and 10 ng; 5 ng; 2 ng; 1 ng; 0.5 ng; 0.1 ng, respectively. Limit of detection was determined with the lowest DNA concentration that gives clear bands (Waturangi, et al, 2015). Specifically, for V. cholerae specificity evaluation was performed in order to confirm whether primer pairs amplify only with the targeted bacteria and do not cross-react with DNA from other species.…”
Section: Sensitivity and Specificity Evaluationmentioning
confidence: 99%
“…Each pathogenic bacterium (V. cholerae, ETEC, and EHEC) were cultured in LB medium for overnight at 37°C using orbital shaker incubator at 120 rpm. Then, 5 mL of drinking water samples were inoculated with 1 mL (0.5 McFarland) of the bacteria suspension for artificial contamination purpose (Waturangi, et al, 2015). Subsequently, the samples were incubated using orbital shaker for 24 hours at 120 rpm in three different temperatures (28 o C, 4 o C, and -20 o C).…”
Section: Screening Of Virulence Gene From Genomic Dna Isolated From Beverage Samplementioning
confidence: 99%